Exercise 9 - Algebraic Operations

You might also like

Download as pdf or txt
Download as pdf or txt
You are on page 1of 17

B'-82 BASIC MATH TUTOR

Algebraic Operations
Algebra is that branch of mathematics that uses letter symbols to represent numbers.
The letter symbols are in essence place holders. They function somewhat like English
words such as someone or somewhere. For exampl�, in the English·sentence "Someone
took the book and put it somewhere," neither the identity of the person in question
nor the new location of the book is known. Using letters in the way algebra does, we
might say "x put the book in y place." The identity of x is unknown, and the new
location of the book is unknown. lt is for this reason that letter symbols in algebra are
often referred to as "unknowns."
Algebra, like English, is a language, and for making certain statements, algebra is
much better than English. For example, the English statement "There is a number
such that, when you add 3 to it, the result is 8" can be rendered more easily in
algebraic notation: x + 3 = 8. In fact, learning the rules of algebra is really very
much like learning the grammar of any language.
With this analogy between algebra as a language and English in mind, let us

.r
begin by studying the components of the language of algebra.

The Basic Grammar of Algebra

l. Terms
The basic unit of the English language is the word. The basic unit of the language of
algebra is the term. In English, a word consists of one or more letters. In algebra, a
term consists of one or more letters (or numbers). For example, x, 2z, xy, N, 2, V7,
and 7T céln all be algebraic terms.
In English, a word·may have a root, a pref1x, a suffix, an ending, and so on. In
algebra, a term may have a coefficient, an exponent, and a sign.

Exponent Exponent Exponent


J, Sign J, J,
2 J, 3 4
coefficient -> · 3x -2b X
i coefficient / j t
variable variable variable

(Note: Just as with numbers, when the sign is positive, the "+" is not written but
understood, e.g., 3x is +3x. Also, when the coefficient is 1, it is unders.tood, not
written out, e.g., x and not 1 x. )
The elements in an algebraic term are all joined by the operation of multiplica­
tion. The coefficient (and its sign) is multiplied by the variable. Thus, -3x means
-3 times x; Sa means (+)5 times a; and fN means f times N.
The exponent, as you have already learned, also indicates multiplication. Thus,
x2 means x times x; a3 means a· times a times a; and N5 means N times N times N
BASIC MATH TUTOR B.:.83

times N times N. When you are working with algebraic terms, be careful not to
confuse the coefficient with the exponent. 3x means 3 times x, while x3 means x
times x times x.
Of course, many terms have both a coefficient and an exponent. Thus, 3x2 means
"3 times (x times x)," and -5a3 means "-5 times (a times a times a)."

2. Expressions
In English, words are organized into phrases. In algebra, terms are grouped togeth�r
in expressions. An expression is a collection of algebraic terms that are joined by
addition, subtraction, or both.

EXAMPLES:
X+ y

-2x + 3x + z
3x2 - 2y2
x2 + y 2

Alge,braic expressions are classified according to the number of terms they contain:
A monomiaf is an expression with a single term.
A pofynomiaf is any expression with more than one term.
A binomfaf is a polynomial with exactly two terms.

3. Equatimis
In algebra, a complete sentence is called an equation. An equation·asserts that two
algebraic expressions are equal.
EXAMPLE:
2x + 4 = 3x - 2
This equation says "2 times a certain Únknown plus 4 is equal to 3 times that unknown
minus 2." (See Equations and lnequalities.)

Basic AJgebraic Operations, j

1. Addition and Subtraction


Addition and subtraction are indicated in algebra, as they are in arithmetic, with the
signs "+" and " - ." In arithmetic, these operations result in the combining of num­
bers into a third number. For example, the addition of 2 and 3 results in the combin­
ing of 2 and 3 to form the number 5: 2 + 3 = 5. In algebra, however, this process of
combining can take place only with /ike terms. Two terms are considered like terms
B-84 BASIC MATH TUTOR

if, and only if, they (1) have exactly the same variable and (2) are raised to exactly the
same power. The coefficient does not determine whether terms are like terms.

EXAMPLES:
3x2 , 40x2 , -2x2 , and V2x2 are like terms.
3x and 3x2 are not like terms.

xy, Sxy, - 23xy, and 'TTXY are like terms.


xy and x2 y are not like terms.

lOxyz, -xyz, and xyz are like terms.


xy, yz, �nd xz are not like terms.

To add or subtract algebraic terms, group like terms and then add or subtract the
coefficients.

EXAMPLES:
What is x2 + 2x2 + 3x2 ?

Ali three terms are like terms: x raised to the second power. To add, simply add
the coefficients: 1 + 2 + 3 = 6. (Remember, a term with no explicit coefficient is
understood to have a �oefficient of 1.) So the result is 6x2 •

What is y+ 2x +3y -x?

Here we have two different types of terms, x and y terms. First, group like terms
together:

(2x - x) + (y + 3y)

(Note: The parentheses are not necessary. They are included just so you can see
clearly how the like terms are grouped.)
"-
Next, add the coefficients for each type of term. For the x terrns, the coefficients are
2 - 1 = 1, and for the y terms, 1 + 3 = 4. So the·final result is 1x + 4y, which is .
written as x + 4y.

EXAMPLES:
What is x - 3x + Sx - 2x?

Here, ali of the terms are like terms, x. Simply add the coefficients: 1 - 3 + 5 -2
= 1, so the result is 1 x, or simply x.

What is 2x - y - 3x + 4y + Sx?

Here, we have both x and y terms. First group like terms:

(2x - 3x + Sx) + (4y - y)


BASIC MATH TUTOR B-85

Now add coefficients for each. For the x terms, 2 - 3 + 5 = 4, and for the y terms 4
- 1 = 3. So the result is 4x + 3y.

What is Sx2 + 3x3 ...:. 2x2 + 4x3 ?

Here, we have two different terms, x2 and x3. Group like terms:

(Sx2 - 2x2 ) + (3x 3 + 4x 3 )

Now add the coefficients for each term. For the x2 terms, the result is 5 - 2 = 3, or
3x2• For the x 3 terms, the resuit is 3 + 4 = 7, or 7x3 • So the final result is 3x2 + 7x3•
Notice that when you have combined all like terms, it is not possible to carry the
addition or subtraction further. For example, x + y is just that, x + y.

2. Exponents
The laws of exponents apply to algebraic terms just as they apply to numbers in
arithmetic. (See Rules for Working with Powers.)

1. To multiply the same variable raised to powers, add the exponents:

2. To divide the same variable raised to powers, subtract the exponents:

x 3 + x 2 = x3
..., 2 = x1 = x

3. To raise an algebraic term to a power, multiply the exponents:


(x 2') 3 = x! 2 H3> = x6

4.. An exponent outside parentheses governs ali terms within the paren­
theses:

3. Multiplication
Multiplication in algebra can be indicated in four ways:
a X b (a)(b) ab

To multiply two or more monomial (single) terms, just multiply their coefficients and
use the laws of exponents.

EXAMPLES:
What is (4x)(2x)?
B-86 BASIC MATH TUTOR

First, multiply the coefficients: (4)(2) = 8. Second, use the law of exponents: (x)(x) =
x 2. So the final result is 8x 2.

What is (3x2)(xy)?
First, multiply the coefficients: (3)(1) = 3. Second, use the laws of exponents: (x2 )(xy)
= x 2+1 y = x 3y. So the final result is 3x3 y.

What is (2xyz)(3xy)(4yz)?

First, multiply the coefficients: (2)(3)(4) = 24. Next, use the laws of exponents:
( xyz)(xy)(yz) = x1 + 1y 1+1+1z1+1 = x2y 3z2. So the result is 24x2y3 z2•

4. Division
To divide one monomial by another, divide coefficients and use the laws of exponents.

EXAMPLES:
What is 4x3 y4 + 2xy3?

First, divide the coefficients: 4 + 2 = 2. Ne�t, use the second law of exponents: x 3y4
...,.. xy 3 = x 3-1 y4-3 � x2 y. So the result is 2x 2 y.

First, divide exponents: 2 -;- 1 = 2. Next, use the second law of exponents: x4 y3 -;- x2z
4 .. · . 2x2y3
= x -2v3 = x2·y3 . So the result
::...__i_
. ,s .
z z. z

5. Fractions
Addition and subtraction of algebraic fractions, like the addition and subtraction of
ordinary fractions, require the use of common denominators.
When you already have like denominators, simply add the numerators of the
fractions, using the already existing denominator.

EXAMPLES:
5 3 5 + 3
-+-=--=­ 8
X X X X

2x x 2x - x x
---=--=-
y y y y
a x a + x
-+-=--
cd
cd cd
BASIC MATH TUTOR Jj..,&;7 .

6. Unlike Denomin.ators
To add or subtract algebraic fractions with unlike denominators, you must first find a
common denominator.

EXAMPLE:
� + ;! + i = 2yz + 3xz + 4xy
x y z xyz

Usually, this can be accomplished by using the "flying x":


� + l = �-+..A l = 2y + 3x
x y x «-'�':.y xy
2x + lt = 2x "-+ ,;rlt = 2x2 + 3y2
y X y ¿�--.,.X xy
To multiply fractions, follow the rules for multiplying arithmetic fractions. Multi­
ply terrns in the numerators to create a new numerator, and multiply terms in the
denorninator to create a new denorninator.

EXAMPLES:
2 3 6
-X-=-
X ,Y xy

X
Q = ab
e d cd
xy
2 3
x x y = xsy�
3 2

z wz wz

To divide algebra.ic fractions, follow the rule for dividing arithrnetic fractions.
lnvert the divisor and multiply..

. EXAMPLES:
�+l=� X �=2X
y X y 3 3y
2x2 + }'.'. = 2x2 � =�
x
y X y y y

[ Multiplying Polynomials 1

A polynornial is an algebraic expression with more than one term, e.g., x + y. A


multiplication problem such as (x + y)(x + y) requires a special procedure.
The fundamental rule for rnultiplying polynomials is that every term of one ex­
pression must be multiplied by every term of the other expression. This principie can
be illustrated using numbers.
B-88 BASIC MATH TUTOR

First, take the case in which a polynomial is to be multiplied by a single term; for
example, 2(3 .t- 4 + 5). One way of solving the problem is to do the addition first
and then multiply:

2(3 + 4 + 5) = 2(12) = 24

lt is also possible, however, to multíply each term in the parentheses by 2 and then
add. Just multiply every term inside the parentheses by the term outside the parentheses:

2(3 + 4 + 5) = (2)(3) + (2)(4) + (2)(5) = 6 + 8 + 10 = 24

Notice that the result is the same no matter which method we use.
Now take the case in which it' i� necessary to multiply two polynomials; for
example, (2 + 3)(1 + 4). Again, this can be accomplished by first adding and then
multiplying:

(2 + 3)(1 + 4) = (5)(5) = 25

But it can also be done by first multiplying and then adding:

(2 + 3)(1 + 4) = (2)(1) + (2)(4) + (3)(1) + _(3)(4) = 2 + 8 + 3 + 12 = 25

We get the same result with either method!


With algebraic expressions such as (x + y), you must use the second method
(multiply and then add), because you cannot add (beyond just saying "x + y"). So
now we will apply the technique to algebraic expressions.

EXAMPLES:
x(y + z) = xy + xz
a(b + e + d) = ab +: ac + ad

The multiplication of two binomials (two two-term expressions) presents a spe­


cial case that arises often enough that you should learn a special technique for han­
dling it. The following diagram illustrates how to multiply two binomials:

..�©-:;
(x + y) (x + y) = x2 + xy + xy + y2 = x2 + 2xy + y2
�®.,,,,,

The method described in the diagram is often referred to as the FOIL method. FOIL is
an acronym for First , Outer, lnner, and Last. Stated more fully, when multiplying two
binomials, e.g., (x + y)(x + y), you first multiply �he first terms together, then the
outer terms together, then the inner terms together, and then the /ast terms together.
Finally, combine like terms.
BASIC MATH TUTOR Jj..,&9;

EXAMPLES:
(x + y)(x + y) =
First: (x)(x) = x2
Outer: (x)(y) = xy
lnner: (y)(x) = xy

Last: (y)(y) = y2
Add: x2 + xy + xy + y2 = x 2 + 2x)' + y2

(x - y)(x - y) =
First: (x)(x) = x 2
Outer: (x)( -y) = - xy
lnner: (-y)(x) = -xy

Last: (-y)(-y) = y2

Add: x2 - xy - xy + y2 = x2 - 2xy + y2
Three situations, including the one just shown, arise with sufficient frequency
that you should memorize thé results so you don't have to do the work:

(x·+ -= (x + y)(x + y) = x 2 +
y¡ 2 2xy + y2
(x - y¡ 2 = (x - y)(x - y) = x2 - 2xy + y2

(x + y)(x - y) = x2 - y2

lt is also possible that you would be asked to multiply sométhing more complex
than two binomials; for example, (x + y)3 . The process is tedious and time-consuming,
but ultimately it is executed the same way. First, multiply (x + y)(x + y), as shown.
above: The result is x 2 + 2xy + y 2 • Then, complete the multiplication by multiplying
every term ·in that result by both x and y, as follows:

(x + y)(x2 + 2xy + y2 ) =
2 2
x(x2 ) + x(2xy) + x(y ) + y(x ) + y(2xy) + y(y ) =
2

x3 + 2x 2 y + xy2 + x2 y + 2xy 2 + y3 =
x3 + 3x2 y + 3xy2 + y3

Factoring

Although mention of the term factoring strikes fear into the hearts of many students,
factoring is really nothing more than the reverse of multiplication. For example, if
(x + y)(x + y) = x2 + 2xy + y2 , then x2 + 2xy + y2 can be factored into (x + y)(x + y).
Fortunately, for purposes of taking the test, any factoring you might need to do will fall into
one of three categories�
10 BASIC MATH TUTOR.

1. Finding a Common Factor.


lf ali the terms of an algebraic expression contain a common factor, then that term
can be factored out of the expression.
EXAMPLES:
ab + ac + ad = a(b + e + d)
abx + aby + abz = ab(x + y + z)

xi + x + x = x (1 + x + x )
3 4 2 2

3a + 6a 2 + 9a3 = 3a(1 + 2a + 3a2)

2. Reversing a Known Multiplicati.on Problem


Sorne patterns recur with such frequency on the exam that you must simply memo­
rize them.

· EXAMPLES:
x2 + 2xy + y2 = (x + y)(x + y)
x2 - 2xy + y2 = (x - y)(x - y)
x 2
- y2 = (x + y)(x - y)

You will .observe that these are the same three patterns you were asked to memorize
above while we were studying the FOIL method.

3. Reversing an Unknown Multiplicatúm Process


Occasionally, and only occasionally, you may find it necessary to factor an expres­
sion that does not fall into one of the two categories ·above. The expression will
almost surely have the form ax2 + bx + e; for example, x2 +· 2x + 1. To factor such
expressions, set up a blank diagram: ( )( ). The diagram is then filled in by
answering a series of questions:
1. What factors will produce the first, the x2 , term?
2. What possible factors will produce the last, the e, term?
3. Which of the possible factors from step 2, when added together, will pro­
duce the middle, the bx, term?
EXAMPLES:
Factor x 2 + 3x + 2.
1. What factors will produce the first, the x2 term? x times x yields x 2, so the
factors, in part, are (x )(x ).
2. What possible factors will produce the last term? The possibilities are (2, 1)
and (-2,-1).
BASICMATHTUTOR B.,9¡

3. Which of the two sets of factors just mentioned, when added together, will
produce a final result of 3x? The answer is (2, 1 ): 2 + 1 = 3. You can confirm
this by performing the multiplication using the FOIL method:

(x + 2)(x + 1) = x 2 + x + 2x + 2 = x 2 + 3x + 2

Factor x2 + 4x - 12.

1. What factors will generate x2 ? . (x )(x


2. What factors will generate -12? (1,-12).(12,-l),(2,-6)(6,¡-2),
(3,-4)(4,-3)
3. Which factors, when added together, will produce the middle term of +4x?
The answer is (6,-2): 6 + (-2) = 4.

So the factors are (x + 6) and (x - 2), a fact that you can confirm by using the
FOIL me,thod to multiply together these two binomials:

(x + 6)(x - 2) = x 2 - 2x + 6x - 12 = x2 + 4x - 12
9: .
B-92 BASIC MATH TUTOR

. EXERCISE

Al.gebraic Operations

1. Which of the following pairs of terms are like terms?


l. 34x and - 18x
11. 2x and 2xy
111. x 3 and 3x
(A) 1 only (B) 11 only (C) 1 and 111 only (D) 11 and 111 only (E) 1, 11, and 111
2. Which of the following pairs of terms are like terms?
l. V2x and V3x
!l. ,r and 10
111. x2 and 2x2
(A) 1 only (B) 11 only (C) 1 and II only (D) 1 and 111 only (E) 1, 11, and 111
3. x + 2x + 3x =
(A) 6x6 (B) x6 (C) 6x (D) x +6 (E) x -6
4. 2x + 3x - x + 4x =
8 11
(A) 8x (B) x (C) 8x (D) _x +8 (E) x - 8
5. a 3 2
+ ª + a =
(A) 3a 3 (B) á3 (C) --
2a 2 · (D) a2 (E) a
3
+ a2 + a
6: z 2 +2z2 -Sz 2 =·
2 2
(A) - 9z (B) - 2z (C) O (D) 2z 2 (E) Sz 2
7. a 3 -12a 3 + 1Sa 3 +2a 3 =
(A) 6a 3 (B) .2a 2 . (C) 6a (D) 3a (E) a
8. 3c + 2a - 1 + 4c - 2a + 1 =
(A) 2a + 4c + 1 (B) 4a + 3c - 2 (C) a +e - 1 (D) 2a + 1 (E) 7c
9. - 7nx + 2nx + 2n + 7x =·
(A) O (B) - Snx + 2n + 7x (C) 18nx (D) 9nx + 9xn (E) 4nx
10. c2 + 2c 2 d1 - c2 =
{A) 4c 2 d2 (B) 2 c 2d2 (C) cl d2 (O) 2cd (E) cd
2
11. 2x + 2x + 2x 2 2
=
6
(A) 6x 6
(B) 2x (C) 6x2 (D) 6x (E) 6
12. 3xy + 3x y - 2xy + y 2
=
(A) 6xy - y (B) x + xy + y (C) 3x2 y + xy + y 2 2
(D) x y + xy (E) 3xy +x
13. x 2
+ 2xy - 3x + 4xy - 6y + 2y + 3x - 2xy + 6y = 2

(A) x2 - 2xy + y 2 (B) x 2 + y2 + 3x + 2y (C) x 2 + 2y2 + 4xy + 6x + 6y


'(D) x 2 + 2y2 + 4xy + 6x (E) x2 + 2y2 + 4xy
14. 8p + 2p 2 + pq - 4p2 - 14p - pq =
(A ) - 2p 2
- 6p (B) - p 2 + 6p (C) 2p 2 + 6p (D) p 2 + 3p (E) 3p 2 - pq
. --B-94., BASIC MATH TUTOR

s 3 2 2
x2 z 3
30. (x l l ) x ( y: : ) =
X y Z xy Z

(A) xyz (8) x2 y2 z 2 (C) x5 y5 z 5 (D) i'y z


6 6
(E ) xyz 12

a b
31. -+-=
e e
ab a+ b
(C) a
+ b + b a+ b
(A) (D) a
e (B)
e 2e c2 (E)
abe

32. � + }:'. + � =
2 2 2
X+y + z X+y+Z X+y+Z
(A) (B) (C ) (O) � (E)�
2 6 8 2 8
ab be ed
33. + + =
X X X
abcd a+b +e+ d ab + be+cd ab + be + ed
(A) (B) (C) (O)
X 3x X 3x
ab + be + ed
(E )
X

x x 3 x4
i
34. -+-+-=
k k k

(A) �
k
9
(B)
X9
3k , (C) T24 (D)
x 2 + x3 + x4
k (E)·
x 2 + x 3 + x4
. 3k

x
35. 2 - }:'. =
z z
(A) � (B) � (C) � (D ) � (E) �
z 2z . x z 2z

36. � + 1'. =
y X
(A) 2L
X+ y . e s> �
y+X (C) �
xy (D)
xy + yx
xy
(E)
.
X2 + y2
xy
a - -b =
37. -
b '\
a
a- b a - ·b ab - ba ª
2 _ b2
(A)� (B) (C) (D) (E)
a - b b - a ab ab ab
x x 2 3
38. -+-=
z
) X2 z + X)y
X +X X2 + x 3
2 5 6
(A) (B) � (C) � (D) (E)
yz yz yz yz yz

39. � + 1'. + � =
a b e
x+y+ z (C) xbc+yac+ zab xbc + yac + zab
(A) � (B) (D)
abe a+b + e abe a+b + e
xa + yb + ze
(E)
abe
v3
x2 =
40. � - ":J
y X
X2 - x3
(A) --.----
x 3 - X2
(B) -�­
x2 - YJ -
(D) X 3 2
5 y5
y y
(C)
x2 _ y2 x y
BASIC MATHTUTOR, B-93'

15. pqr + qrs + rst + stu·=


(A) pqrst (B) pq + qr + rs + st + tu (C) pqr + rst (O) 4pqrst
(E) pqr + qrs + rst + stu
2 3
16. (x )(x ) =
5
(A) x1 (8) x (C) x; (0) x (E) x
6

17. (a)(a2 )(a3 )(a4 ) =


(A) 1 Oa (B) 24a (C) a5 (D) a10 (E) a 24
18. y + y2 =
s

(A) 3 y (B) 7 y t (0) y)


7
(C) y (E) y
19. (x 2y )(xy 2) =
(A) 4x y (8) x 3y 3 (C) xy4 (D) x4 y4 (E) xy 1&
20. (abc)(a 2bc2) =
(A) 4abc (B) a bc
2 2
(C) a 3b 2c3 (D) a·1b 3c 3 (E) abe"
21. (xy2 )(x 2 z)(y2 z) =
(A) Bx yz (8) x 2y4 z (C) x 3y4 z 2 (0) x 3y3 z2 (E) x 3y3 z3
x2y4
=
xy
22.

(A) y
3
(8) xy3 (C) x 2 i1 (D) x:i y" (E ) xy11
a3 b4 c s =
23. --
abe
(A) a b e
2 3 4
(8) a 3 b4c 5 (C) (abd (D) (abe) 12 (E) (abe)60
24. (x 2y3 )4 =
(A) (xy)9 (8) x6y7 (C) xs y1 2 (D) xy20 (E) xy24
a2
25. (
· Pr=
a"
a5 b a6b a6b9
5
(A)�
b
(B) íj9 (C) (D) (E)

x �z s =
3

X y Z
26.
4
yz
¡

y 2 z4 (B) x y2 z4
2 i r,
' z"
(A) (C) � (O) (E) y'
4 d2
(e
X X X

r=
27. e2d
(A) e 5 d3 (B) e sd s
(C) c6d 3 (D) c"d4 (E) e <'cf'

28. =
(�)x(�)
(A) x 2y 3 (B) x3y
4
(C) x3 y s
(D) xV' (E) x" y7

abc2 ª 2b2e
29 ( 3) x ( ab ) =
· abc
.ib be C) ab
(A) ( D) e (E) 1
e (B) a (

_
Bz96 BASIC MATH TUTOR

54. (a + b) (e + d) =
(A) ab+be+ed
(8) ab+be+ed + ad
(C) ae + bd
(D) ae + ad + be + bd
(E) ab + ae + ad

55. (w + x) (y - z) =
(A) wxy - z
(B) wy + xy - yz
(C) wy - wz + xy + xz
(D) wy + wz + xy - xz
(E) wy - wz + xy - xz

56. (x + y) (w + x + y) =
(A) x2 + wx + wy + xy
(B) x2 + y2 + wx + wy + 2xy
(C) _x2 + y 2 + wxy
(D) x 2 + y 2 + wx 2 y2
(E) x2y2 + wxy

57. (2 + X) (3 + X + y) =
(A) x2 + 6xy '+ 6
(B) x2 + 6xy + 3x + 2y + 6
(C) x + 2xy + 6x + 6y + 6
2

(D) x2 + xy + Sx + 2y + 6
(E) x2 + 3xy + 2x + y + 6

58. (x + y) 3 =
(A) x 3 + 5x 2 y + y 2 z + xyz
(B) x 3 + 3x3 y + · 3xy 3 + y 3
(C) x 3 + 3x2y +. 3xy2 + y3
(D) x3 + 6x2y2 + Y J
(E) x 3 + 12x2y 2 + y3

59. (x - y) 3 =
(A) x 3 - 3x2y + 3xy2 - y3
(B) x' + 3x 2 y + 3xy 1 + y 1
(C) x 3 + 3x2y .:... 3xy2 - y3
(D) xJ + 6x2y2 + YJ
(E) x:i + 6x 2y 2 - y1

60. (a + b) (a - b) (a + b) (a _: b) =
(A) 1 (8) a 2 - b 2 (C) a 2 + b 2
(D) a - 2a2 b2 + b4 (E) a 4 + 2a2b2 + b4
4

61. 2a + 2b + 2e =
(A) 2(a + b + e) (B) 2(abe) (C) 2(ab + be + ca)
(D) 6(a + b + e) (E) 8(a + b + e)
62. x + x 2 + x 3 =
(A) x(x + 2x + 3x) (B) x(l + 2x + 3x) (C) X( 1 + 2 + 3)
(O) x(l + x + x 2 ) (E) x(l + 3x)
BASIC MATH Tl!TOR B-95

41. 2(x + y) =
(A) 2xy (B) 2x + 2y (C) 2 + x + y
(D) 4xy (E) 2x 2 + 2y2
42. a(b +e)=
(A) ab + be (B) ab + ac (C) 2abc
(D) ab 2 + b 2c (E) ab + �e + be

43. 3(a + b + e + d) =
(A) 3abcd (B) 3a + b +e+ d (C) 3a + 3b + 3c + 3d
(D) 3ab + 3bc + 3cd (E) 12a + 12b + 126 + 12d
44. 2x(3x + 4x 2 ) =
3
(A) x10 (B) 6x + 8x 2 (C) Sx 2 + 6x
2 2
(D) 6x + 8x 3
(E) 6(x + x )
3

45. 3a2 (ab + ac + Ú) =


(A) 3a3 b2 e
(B) 3a3 + 3b 2 + 3c
(C) 3a 2b + 3a2 c + 3a 2 bc
(D) 3a3b + 3a3 c + 3a2 bc
(E) 3a5 b + 3a5 c

46. (x + y) (x + y) =
(A) x 2 + y'2 (B) x 2 - y2 (C) x 2 + 2xy - y2
(D) x 2 - 2xy + y 2 (E) x 2 + 2xy + y 2

47. (a+ b) 2 =
(A) a + b 2 (B) éi 2
2 - b2 (C) a 2 + 2ab - b2
(D) a2 - 2ab + b2 (E) a 2 + 2ab + b 2

48. (x - y) 2 =
(A) x 2 + 2xy - y2 · (B) x2 ·+ 2xy + y 2 (C) x 2 .- 2xy + y2
(D) x 2 - 2xy - y2 (E) x2 + y 2
.

49. (a + b) (a - b) =
(A) a 2 - b2 (B) a2 + b 2 (C) a2 + 2ab + b2
(D) a2 - 2ab +"\.b
2
(E) a + 2ab - b 2
2

50. (X - 2) 2 =
(A) 2x (B) 4x (C) x2 - 4
(D) x 2
- 4x + 4 (E) x2 - 4x - 4
51. (2 - x) 2
=
(A) 4 - x 2 (B) x 2 + 4 (C) x2 + 4x + 4
(D) x 2 - 4x + 4 (E) x 2 - 4x - 4
52. (ab + be) (a+ b) =
(A) a 2 b + ab 2 + b2e + abe
(B) a 2b + ab 2 + abe
(C) a 2 b + ab 2 + a 2 be
(D) a2 b + ab +be+ abe
(E) a 2 + b2 + c 2 + abe

53. (x - y) (x + 2) =
(A) x 2 + 2xy + 2y (B) x 2 + 2xy + x + y (C) x2 + 2xy + x - 2y
(D) x 2 - xy + 2x - 2y (E) x 2 + 2x + 2y - 2
BASIC MATH TUTOR 96

63. 2x2 + 4x + 8x =
3 4

(A) 2x1(1 + 2x + 4x2) (B) 2x1(1 + 2x+4x3 ) (C) 2x2 (x+2x+4x2 )


4
(D) 2x2(x+2x2+4x 3 ) (E) 2x2(x1+2x3+4x )
64. abe+ bed + ede =
(A) ab(e+d+ e) (B) ae(b+ e) (C) b(a+e+de)
(D) e(ab+bd + de) (E) d(a+b + e+e)
65. x2 y2 + x2y + xy2 .=
(A)(x + y)2 (B) x + y
1 2
(C) x2y2(x + y)
(D) xy(xy + x + y) (E) xy(x + y + 1)
66. p2 + 2pq + q 2 =
(A) (p+q) (p - q) (B)(p+q) (p+q) (C) p2 - q2
(D) p2 + q 2 (E) (p - q)2
67. 1442 - 121 2 =
(A) 23 (B)(144 + 121)(144 - 121) (C)(144 + 121)(144 + 121)
(D)(23)2 (E)(144 + 121)2
68. x 2 - y2 =
(A)(x+ y)(x - y) . (B)(x+y)(x+y) (C)(x - y)(x - y)
(D) x2 + y2 (E) 2xy
69. x2 + 2x + 1 =
(A)(x+1)(x - 1) (B)(x+1)(x+1i (C)(x - 1)(x - 1)
(D) x 2 .:_ 1 (E) x2 + 1
70. x 2 - 1 =
(A)(x -i- 1)(x + 1) · (B)(x - 1)(x - 1) (C)(x + 1)(x - 1)
(D)(x - 1)2 (E)(x + 1)2
71. x2 + 3x+2 =
(A)(x + 1)(x - 2) (B)(x + 2)(x + 1) (C)(x+2) (x - 1)
(D)(x - 2)(x - 1) (E)(x+:3) (x - 1)
72. a 2 - a - 2 =
· (A)(a+2)(a - 1) (B) (a - 2)(a + 1) (C)(a+1)(a + 2)
-4'
(D)(a + 2)(a - 2) (E) (a+1)(a - 1)
\.
n:· p2 + 4p+3 =
(A)(p+3)(p+l) (8) (p + 3) (p - 1) (C) (p -·'3) (p - 1)
(D) (p + 3)(p +4) (E)(p + 3) (p - 4)
74. e2+6e + 8 =
(A)(e+2)(e+4) (8) (e+2)(e - 4) (C)(e+4)(e - 2)
(D)(e+3)(e+ 5) (E)(e+8)(e - 1)
75. x 2 + X - 20 =
(A)(x + 5)(x - 4) (8)(x + 4)(x - 5) (C) (x + 2)(x - 10)
(D)(x + 10)(x - 2) (E)(x + 20)(x - 1)
76. p2 + 5p + 6 =
(A)(p + 1)(p + 6) (8)(p + 6) (p - 1) (C)(p + 2) (p + 3)
(D) (p - 3)(p - 2) (E)(p + 5)(p+1)
77. x2 +Bx + 1 6 =
(A) (x+2) (x+8) (B) (x+2) (x - 8) (C) (x - 4) (x - 4)
(D) (x+4) (x - 4) (E) (x+4) (x+4)
B-98 BASIC MATH TUTOR .

78. x2 - Sx - 6 =
(A) (x + 1) (x + 6) (8) (x + 6) (x - 1) (C) (x + 2) (x + 3)
(D) (x - 6) (x + 1) (E) (x - 2) (x - 3)

79. a 2 - 3a + 2 =
(A) (a - 2) (a - 1) (B) (a - 2) (a + 1 ). (Q (a + 1) (a - 2)
(D) (a - 3) (a + 1) (E) (a + 3) (a + .1)

80. x2 + X - 12 =
(A) (x + 6) (x + 2) (B) (x + 6) (x - 2) (C) (x + 4)·(x - 3)
(D) (x - 4) (x - 3) (E) (x + 12) (x + 1)

�------

You might also like